Latin Literature. (April 2019) - Whitton, Christopher
Abstract : Nos ausi reserare… ('We dare unbolt…'): a small but weighty beginning, with the new Loeb Ennius. It's nearly eighty years since E. H. Warmington finished his four-volume Remains of Old Latin (1935–40), combining the fragments of Ennius, Lucilius, Accius, and other pre-Sullan poetry in cheerful farrago with the Twelve Tables and a book of 'archaic inscriptions'. The dry title notwithstanding, this was a flagship collection from a long-serving general editor of the Loeb Classical Library (1937–74): the scholarship was valiant, despite the slips so fully catalogued by unkinder reviewers, and the product has exerted wide influence as the go-to 'accessible' edition of so much important material – even if l'Année Philologique insists on calling its editor 'Brian' (his son: talk about tuer le père ). Still, eighty years are a long time even in Classics, and an update could fairly be called overdue; happy news, then, that Harvard have commissioned Gesine Manuwald, another London professor, to oversee it. The new title is Fragmentary Republican Latin, more of a mouthful but a touch less downbeat; the remit is extended to include oratory and historiography; and the first instalment is a chunky Ennian diptych (one book for the Annals, one for the rest), jointly curated by Manuwald and Sander M. Goldberg.